2017
DOI: 10.1097/phh.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Municipal Officials' Involvement in Transportation Policies Supportive of Walking and Bicycling

Abstract: Context Local transportation policies can impact the built environment and physical activity. Municipal officials play a critical role in transportation policy and planning decisions, yet little is known about what influences their involvement. Objective To describe municipal officials’ involvement in transportation policies that were supportive of walking and bicycling and to examine individual- and job-related predictors of involvement in transportation policies among municipal officials. Design A cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Moreover, it may not be enough to involve key stakeholders from other sectors in HEPA promotion. Studies have highlighted that the awareness of HEPA importance by elected officials and department heads from various sectors determine their involvement in HEPA promotion [25,26]. Strong leadership and strong political advocacy might therefore help enhance the development of intersectoral HEPA polices [53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it may not be enough to involve key stakeholders from other sectors in HEPA promotion. Studies have highlighted that the awareness of HEPA importance by elected officials and department heads from various sectors determine their involvement in HEPA promotion [25,26]. Strong leadership and strong political advocacy might therefore help enhance the development of intersectoral HEPA polices [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Involvement in intersectoral policies may be limited when policy-makers lack an understanding of the benefits of this approach and have different policy priorities based on their sector [18,24]. Their perceptions of the importance of HEPA policies, especially when they come from different sectors, may be an indicator of their willingness to become involved [25,26]. Studies have shown that capturing the views of policy-makers and professionals across multiple sectors therefore provides a deeper understanding of the key factors that facilitate intersectoral collaborations and HEPA policy implementation [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Municipalities have a significant role in the planning and development of communities that support active living (Zwald et al, 2014), which aligns with health sector priorities to promote physical activity and reduce the burden of chronic diseases (World Health Organization, 2010). For many local governments, fiscal evidence on the benefits relative to the costs of investment is one consideration in financing AT infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…These complexities in collaboration, coordination, and jurisdictions can also create potential roadblocks, independent of the level of public support for such policy or programmatic initiatives. 36 This study uses a cross-sectional design and therefore precludes assessment of causal associations or the potential impact of residential self-selection. Additionally, the sample was not nationally representative but rather purposefully selected from counties based on higher or lower levels of county-level population health-related risk factors of obesity and insufficient activity known to be associated with active transportation behaviors.…”
Section: Discussionmentioning
confidence: 99%